Influence Analysis of Lubricant Recesses on the Working Capacity of the Bridge Span Spherical Bearing - Yuriy O. Nosov; Anna A. Kamenskikh (Lubricants, 2022)
The load on transport and logistics systems is increasing every year. This is due to car park growth around the world. Thus, increasing bridge structure durability is an urgent task for bridge-building companies. This study analyses the contact deformation of spherical bearing elements through an anti-friction polymer layer with different geometrical configurations of recesses for the lubricant, i.e., annular grooves and spherical holes. The material of the anti-friction layer (a modified polytetrafluoroethylene (PTFE)) is modelled within the framework of the deformation theory of plasticity. The procedure of automating the numerical model construction depends on the input parameters, including the thickness of the layer, the basic geometrical parameters of the recesses for the lubricant, and the distance between the rows of recesses, etc. The influence of the arrangement of filling sliding anti-friction layers on recesses for lubricants in the form of spherical holes on the contact deformation behaviour of bridge bearings has been considered. The reduction of lubricant volume in the sliding anti-friction layer with the geometry of recesses in the form of spherical holes ranges from 26 to 48.4%, depending on the filling scheme, has been found. In this case, structures with lubrication recesses in the form of spherical holes have several advantages, including a more uniform distribution of contact parameters in the interface areas of the steel plates with the anti-friction layer, reduction of the maximum level of the plastic deformation intensity, displacements along the normal relative to the free end of the sliding layer, and the settlement of the bearing.